What Are the Data Requirements for AI Drug Discovery? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Artificial intelligence (AI) is rapidly transforming the landscape of drug discovery, promising to accelerate the development of new therapies and reduce the...
Keywords: Drug Discovery and Pharmaceutical AI; Requirements; Discovery; Artificial Intelligence